Manajemen Kepemimpinan Kepala Sekolah dalam Perencanaan Berbasis Nilai-Nilai Kristiani - Yanti Y. E. Sole; Marlen A. Daik; Sem Saetban; Januar D. M. Rohi; Sulifertia Saekoko (Kelola: Jurnal Manajemen Pendidikan, 2025)
The success or failure of education and learning at school is greatly influenced by the principal's ability to manage each component of the school, one of which is planning. This research aims to examine the Leadership Management of School Principals in Planning Based on Christian Values at SMTK in District. Rote Ndao. This research used a descriptive qualitative approach with a multisite design involving two research sites, namely, SMTK Rote Timur and SMTK Ba'a. The main informants in this research consisted of 4 people from each school consisting of the principal, deputy principal, teachers and staff, so it becomes 8 informants involved. Data collection techniques include participant observation, interviews and documentation studies, while data analysis techniques used consist of: 1) single site analysis consisting of data collection, data reduction, data presentation and drawing conclusions; 2) cross-site analysis. This research used data triangulation technique as the data validation techniques. Therefore, the results of the research showed that the leadership management of school principals in planning based on Christian values as described in Galatians 5: 22-23 has been implemented in the leadership of SMTK principals throughout the district Rote Ndao. Christian-based values are depicted in the form of the school's vision and mission and are integrated and concretized in academic and non-academic programs. Therefore, it is hoped that school principals can outline program plans guided by a vision and mission based on Christian values ​​integrated into the planning.